Disruption of zinc homeostasis reverses tigecycline resistance in Klebsiella pneumoniae - Jinyu Wang; Jinyu Wang; Cuiping Xia; Cuiping Xia; Zhaoxin Xia; Zhaoxin Xia; Jilu Shen; Jilu Shen (Frontiers in Cellular and Infection Microbiology)
IntroductionZinc exhibits potent antimicrobial properties due to its ability to compromise bacterial structure and protein functionality, effectively inhibiting and eradicating bacteria. However, bacteria have evolved mechanisms to expel excess zinc ions from their cells, enabling them to thrive in environments rich in metal ions at high concentrations. This evolutionary advancement limits the clinical application of metal ions as antimicrobial agents. In this study, we aimed to investigate the potential of zinc ionophores to overcome bacterial resistance by elevating intracellular zinc ion levels.MethodsWe employed the zinc ionophore PBT2 to elevate intracellular zinc ion levels in Klebsiella pneumoniae, a bacterium known for its resistance to various antibiotics. By treating K. pneumoniae with PBT2, we aimed to assess its impact on bacterial resistance to tigecycline, an antibiotic commonly used in clinical settings. The changes in intracellular zinc ion levels, superoxide dismutase activity, reactive oxygen species concentration, and cell wall synthesis pathway were monitored to evaluate the mechanism of action of PBT2.ResultsOur results revealed that PBT2 successfully reversed the resistance of K. pneumoniae to tigecycline. Specifically, PBT2 increased the concentration of intracellular zinc ions in K. pneumoniae, leading to a suppression of superoxide dismutase activity within the cell and an elevation of reactive oxygen species concentration. These changes impaired the oxidative stress response of the bacteria. Additionally, the disruption of zinc homeostasis significantly inhibited the cell wall synthesis pathway in K. pneumoniae, potentially restricting the efflux pump mechanism that predominantly drives tigecycline resistance.DiscussionThe findings of this study pave the way for innovative strategies and approaches in the clinical development of novel antimicrobial agents. By using zinc ionophores such as PBT2 to elevate intracellular zinc ion levels, we can overcome bacterial resistance to antibiotics like tigecycline. The suppression of superoxide dismutase activity and elevation of reactive oxygen species concentration suggest that PBT2 impairs the oxidative stress response of K. pneumoniae, further enhancing its susceptibility to antibiotics. Furthermore, the inhibition of the cell wall synthesis pathway and restriction of the efflux pump mechanism provide additional mechanisms by which PBT2 reverses antibiotic resistance. These results highlight the potential of zinc ionophores as a novel class of antimicrobial agents and warrant further investigation into their clinical applications.